Jovens em conflito com o Estado: etnografias da reinserção escolar nas medidas socioeducativas - Barbosa, Pamela Karem Zaparolli (2020)
This ethnography aims to reflect on the school reinsertion of young people in compliance with socio-educational measures in an open environment (MSE-MA), in response to the demands of re-socialization present in ECA and SINASE and required by the Judiciary. The effort is to understand the ways in which young people experience the practice of compulsory school reinsertion taking into account the different trajectories and relationships woven and legitimized in the tangle of institutions present in this plot. In addition, I propose to problematizing the notion of socio-education as a punitive method for a possible re-socialization and how these terms are placed in the context of this dissertation where school reintegration plays a fundamental role. The research was carried out in three stages and in MSE-MA services located in three peripheral regions of the city of São Paulo, with three different modes of insertion in the field. The insertions and the actions in each three of the research stages, first as a technique in the implementation of the MSE-MA, later as an educator and later as a researcher, are problematized and deepened as ethnographic experiences. For this reason, I designated my ethnographic production in three times: three different perspectives in different chronological and spatial times.